Newnes short wave listening handbook - Pritchard, Joe (Heinemann Newnes, 1989)
Newnes Short Wave Listening Handbook is a guide for starting up in short wave listening (SWL). The book is comprised of 15 chapters that discuss the basics and fundamental concepts of short wave radio listening. The coverage of the text includes electrical principles; types of signals that can be heard in the radio spectrum; and using computers in SWL. The book also covers SWL equipment, such as receivers, converters, and circuits. The text will be of great use to individuals who want to get into short wave listening.